A Pragmatist Defence of the Ban on Torture: From Moral Absolutes to Constitutive Rules of Reasoning. (October 2016) - Thaler, Mathias
This article seeks to contribute to the growing literature on pragmatism in political theory by revisiting the role of moral absolutes in politics. More specifically, it proposes the idea that pragmatism can support a particular defence of the ban on torture. In contradistinction with deontological accounts, it will be argued that the principles underlying the ban on torture should not be construed as transcendental values that impose external constraints on political action, but as constitutive rules that emerge from, and are sustained by, a web of intersecting social practices. While pragmatists vehemently reject the introduction of absolutes in politics, their anti-foundationalist conception of reasoning crucially hinges on the sustainability of adjustable banisters along which judgements are formed. The article suggests that the torture prohibition ought to be reinterpreted as one such banister.